Up-regulation of activating and inhibitory NKG2 receptors in allogeneic and autologous hematopoietic stem cell grafts - Picardi, Alessandra (J Exp Clin Cancer Res, 2015)
BACKGROUND: Hematopoietic Stem Cell Transplantation (HSCT) is known to induce the inhibitory immune receptor NKG2A on NK cells of donor origin. This occurs in allogeneic recipients, in both the haploidentical and HLA-matched settings. METHODS: To gain further insight, not only NKG2A, but also the activating receptors NKG2C and NKG2D were assessed by flow cytometry. Immunophenotyping was carried out not only on CD56(+) but also on CD8(+) lymphocytes from leukemia and lymphoma patients, receiving both HLA-matched (n = 7) and autologous (n = 5) HSCT grafts. Moreover, cognate NKG2 ligands (HLA-E, MICA, ULBP-1, ULBP-2 and ULBP-3) were assessed by immunohistochemistry in diagnostic biopsies from three autotransplanted patients, and at relapse in one case. RESULTS: All the NKG2 receptors were simultaneously up-regulated in all the allotransplanted patients on CD8(+) and/or CD56(+) cells between 30 and 90 days post-transplant, coinciding with, or following, allogeneic engraftment. Up-regulation was of lesser entity and restricted to CD8(+) cells in the autotransplantation setting. The phenotypic expression ratio between activating and inhibitory NKG2 receptors was remarkably similar in all the patients, except two outliers (a long survivor and a short survivor) who surprisingly displayed a similar NKG2 activation immunophenotype. Tumor expression of 2 to 3 out of the 5 tested NKG2 ligands was observed in 3/3 diagnostic biopsies, and 3 ligands were up-regulated post-transplant in a patient. CONCLUSIONS: Altogether, these results are consistent with a dual (activation-inhibition) NK cell re-education mode, an innate-like T cell re-tuning, and a ligand:receptor interplay between the tumor and the immune system following HSCT including, most interestingly, the up-regulation of several activating NKG2 ligands. Turning the immune receptor balance toward activation on both T and NK cells of donor origin may complement ex vivo NK cell expansion/activation strategies in unmanipulated patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13046-015-0213-y) contains supplementary material, which is available to authorized users.